Respuesta :
Answer:
The equation has only one solution which is:
- [tex]x = 10[/tex]
Step-by-step explanation:
Given the equation
[tex]3x\:+\:6\:=\:-1\:-\:3\:+\:4x[/tex]
Let us solve the equation to determine the type of the equation
[tex]3x\:+\:6\:=\:-1\:-\:3\:+\:4x[/tex]
subtract the number: -1 - 3 = -4
[tex]3x+6=4x-4[/tex]
subtract 6 from both sides
[tex]3x+6-6=4x-4-6[/tex]
[tex]3x=4x-10[/tex]
subtract 4x from both sides
[tex]3x-4x=4x-10-4x[/tex]
[tex]-x=-10[/tex]
Divide both sides y -1
[tex]\frac{-x}{-1}=\frac{-10}{-1}[/tex]
[tex]x=10[/tex]
Therefore, the equation has only one solution which is:
- [tex]x = 10[/tex]